2004
DOI: 10.1126/science.1097789
|View full text |Cite|
|
Sign up to set email alerts
|

Self-Assembled Hexa- peri -hexabenzocoronene Graphitic Nanotube

Abstract: An amphiphilic hexa-peri-hexabenzocoronene self-assembles to form a pi-electronic, discrete nanotubular object. The object is characterized by an aspect ratio greater than 1000 and has a uniform, 14-nanometer-wide, open-ended hollow space, which is an order of magnitude larger than those of carbon nanotubes. The wall is 3 nanometers thick and consists of helical arrays of the pi-stacked graphene molecule, whose exterior and interior surfaces are covered by hydrophilic triethylene glycol chains. The graphitic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
733
1
10

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,026 publications
(766 citation statements)
references
References 19 publications
22
733
1
10
Order By: Relevance
“…48 Two terminal hydrophilic groups of different size glucopyranose and carboxylic acid headgroups were covalently linked to an oligomethylene spacer (carbon numbers ¼ 12À20). Self-assembled organic nanotubes from 1(14), 1(16), 1 (18), and 1 (20) possess inner diameters in the 17.7À22.2 nm range at intervals of $1.5 nm, with an increment of two carbons in the spacer chains (Fig. 5).…”
Section: Asymmetric Organic Nanotubes With Different Inner and Outer mentioning
confidence: 99%
See 2 more Smart Citations
“…48 Two terminal hydrophilic groups of different size glucopyranose and carboxylic acid headgroups were covalently linked to an oligomethylene spacer (carbon numbers ¼ 12À20). Self-assembled organic nanotubes from 1(14), 1(16), 1 (18), and 1 (20) possess inner diameters in the 17.7À22.2 nm range at intervals of $1.5 nm, with an increment of two carbons in the spacer chains (Fig. 5).…”
Section: Asymmetric Organic Nanotubes With Different Inner and Outer mentioning
confidence: 99%
“…Recently, supramolecular chemical procedure enabled the self-assembly of graphitic nanotubes from hexabenzocoronene amphiphiles derivatized from a partial section of graphene. 20 Those nanotubes are of great interest in terms of possibly sharing the properties of CNT and LNT. [24][25][26] …”
Section: Nanotubes With 10 Nm Inner Diametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Aida and co-workers 55 showed that amphiphilic HBCs (having a mini Janus plane, Figure 4a) have distinctly different assembly properties than HBCs with any other substitution pattern. Specifically, HBCs bearing two pseudo-cis alkyl chains and two pseudo-cis TEG chains selfassemble into hollow nanotubes by p-stacking in tetrahydrofuran.…”
Section: Hbc-based Triads For Electron Transfermentioning
confidence: 99%
“…[6][7][8][9][10] Controlled ordering of the self-assembled architectures requires skillful design of molecular constituents. Successful examples are spherical to tubular or cylindrical assemblies formed by attaching chiral handles 11,5,[12][13][14][15][16] or by the sergeant-and-soldiers [17][18][19][20] coassembly approach. More recently, a rare transition from vesicles to helical tubules has been obtained by sergeant-and-soldiers coassembly of chiral and achiral oligo(p-phenylene-ethynylene) derivatives.…”
Section: Introductionmentioning
confidence: 99%